Spontaneous abortion in women occupationally exposed to inhalational anesthetics: a critical systematic review - Oliveira, Lara A. [UNESP] (2021)
Occupational exposure to inhalational anesthetics has been associated with health problems, including reproductive issues. Considering the scarcity and outdated nature of reviews concerning this relevant topic, which has implications for indoor pollution/environmental science/public health, this critical review aimed to systematically evaluate whether exposure to inhalational anesthetics is associated with abortion. Seven databases were searched with no language or year restrictions. Of the 3881 search results, 18 observational studies were included. Some studies demonstrated a significant association between occupational exposure to inhalational anesthetics and spontaneous abortion, especially among professionals who work for longer periods and/or in an environment without gas scavenging/ventilation systems, which may favor the occurrence of abortion in this population. Due to considerable heterogeneity and limitations, it cannot be concluded whether an association exists between occupational exposure to anesthetics and the occurrence of abortion. However, more well-designed studies should be performed, especially in less economically developed countries that do not have access to quality anesthetic gas scavenging/ventilation systems, thereby bringing this issue into sharp focus. This review highlights the need for scientific knowledge in this area and the extensive use of scavenging equipment and in the workplace to minimize exposure and reduce the risk of abortion.